Membangun Generasi Berkarakter Qur'ani di Tengah Genosida: Studi Metode Pendidikan al- Quran dalam Keluarga Gaza Palestina - Yudelnilastia Yudelnilastia; Adriansyah Adriansyah; Muh. Fauzi; Widia Agustin (ALSYS, 2026)
Although Qur’anic education within the family has been widely studied, research specifically examining methods of Qur’anic education for developing children’s character amid genocide, particularly among families in Gaza, Palestine, remains limited. This study aims to analyze the methods of Qur’anic education implemented within Gazan families and their contribution to the development of Qur’anic character and children’s spiritual-social resilience amid prolonged conflict. This study employed a qualitative approach with a library research design. Data were collected through the documentation of journal articles, books, reports from international organizations, and relevant literature and were then analyzed using content analysis. The results showed that Qur’anic education within Gazan families was implemented holistically through parental role modelling, the habituation of reading and memorizing the Qur’an, and the internalization of Qur’anic values in daily life, reinforced by the roles of mosques, halaqah tahfiz, and community support. The use of Arabic as the mother tongue also supported the process of understanding and memorizing the Qur’an. Qur’anic education functioned not only as a means of transmitting religious knowledge but also as a coping mechanism for conflict-related trauma and a foundation for developing a generation that is resilient, patient, morally upright, and characterized by Qur’anic values. This study concludes that family-based Qur’anic education plays an important role in developing children’s spiritual resilience and character amid a humanitarian crisis. Theoretically, these findings expand the study of Islamic education, character education, and Qur’anic education in conflict contexts, while practically, they can serve as a basis for families, Islamic educational institutions, humanitarian organizations, and policymakers in designing adaptive educational models for children in conflict-affected areas.